Digital tools in the development of social skills: The role of the teacher as facilitator - Núñez-Naranjo, Aracelly; Sánchez-Torres, Adriana (International Journal of Innovative Research and Scientific Studies, 2025)
The paper analyzes the role of the teacher in the development of social skills of seventh and eighth grade students through the integration of digital tools. The aim was to evaluate the impact of technology-mediated pedagogical strategies on the social and academic development of students. A quasi-experimental design with a mixed approach was used; a pretest-posttest was applied to a control group (traditional teaching) and an experimental group (digital tools: Educaplay, Kahoot, Genially, Google Meet). A validated CHASO questionnaire and classroom observation sheets were applied, assessing social skills and teaching practices. SPSS was used (t-tests, Kolmogorov-Smirnov), and qualitative data were analyzed thematically. The experimental group showed a significant improvement in social skills and academic performance compared to the control group. Technological tools enhanced motivation, although individual challenges persisted. The teaching guide mediated the use of technology and fostered empathetic and collaborative environments. The integration of digital tools in the classroom effectively promotes the development of social skills and digital competencies. However, it may vary due to individual and contextual factors, and teacher intervention is necessary. Curricular designs that promote the integration of digital tools in the classroom are recommended.